Efectos de la victimización, percepción de riesgo y vulnerabilidad en el miedo al delito: un estudio en jóvenes universitarios mexicanos - Reyes-Sosa, Hiram (2025)
Violence and insecurity associated with drug trafficking have generated high levels of crime in Mexico. The latter has led to an increase in crime rates among society and, furthermore, to a large part of the population perceiving insecurity and victimization as two of the country’s main problems. This article proposes an explanatory and psychosocial model to study fear of crime in Mexico. In order to achieve this, the perspectives of victimization, risk perception and vulnerability are addressed. A total of 443 university students participated in the study (49.9% men and 50.1% women) with a mean of 21.32 years (SD = 2.23). The results showed that having been a victim of a crime (victimization) and the perceived risk perception (contextual) further promote concern about the crime. In relation to gender (vulnerability), it was found that women are more concerned than men about becoming a victim of a crime, particularly women perceive that the consequences of crime are more negative for their group of belonging.